HUBUNGAN PEMANFAATAN PERPUSTAKAAN SEKOLAH DENGAN MINAT BACA SISWA SDN 83 SINGKAWANG - Meli Napisa; Evinna Cinda Hendriana; Mertika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study's objective is: 1) to explain how the school library is used to grade V students of SDN 83 Singkawang; 2) to describe the reading interest of grade V students of SDN 83 Singkawang; 3) to ascertain the degree of the correlation between grade V students at SDN 83 Singkawang's library use and their interest in reading. Correlation with quantitative approaches is used in this study. Students from SDN 83 Singkawang made up the study's population. The research sample was taken in class V which consisted of two classes Va and Vb. The normalcy test using the Chi-squared calculation is the prerequisite test that is run. Data were subjected to univariate analysis at the 5% (0.05) significance level. The Pearson product moment correlation method was applied to evaluate the hypothesis. According to the findings; 1) from the calculation of the overall average score of the utilization of the SDN 83 Singkawang school library is quite good. 2) from the calculation of the overall score of reading interest of grade V students on average 71.96%, it may be inferred that grade V students at SDN 83 Singkawang have a good category level of interest in reading. 3) utilizing the school library and pupils' interest in reading are significantly correlated, with a determinant coefficient of 59.29% and a correlation value of 0.770.